2007
DOI: 10.1093/jnci/djk135
|View full text |Cite
|
Sign up to set email alerts
|

The 1p-Encoded Protein Stathmin and Resistance of Malignant Gliomas to Nitrosoureas

Abstract: Loss of heterozygosity for the stathmin gene may be associated with improved outcomes of patients with 1p+/- anaplastic oligodendroglioma tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…[15][16][17] STMN1 knockdown also produced an additive to synergistic interaction with chemotherapeutic agents such as the taxanes. [18][19][20] The bi-sh-STMN1 incorporates two stem-loop structures in an expression construct promoting both cleavagedependent and cleavage-independent RNA-induced silencing complex (RISC) assemblies thereby generating RISC-associated mature effector small RNAs with multiple independent gene silencing activities. On the basis of the observation that miRNAs are associated with both non-nucleolytic (Ago1, 3,4) and nucleolytic Ago2-containing RISC and siRNAs with the nucleolytic Ago2, the novel bifunctional strategy specifically promotes the loading of miRNA-like effector molecules onto the cleavage-independent RISC as well as the accumulation of siRNA effector molecules by the cleavagedependent (Ago2 containing) RISC.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] STMN1 knockdown also produced an additive to synergistic interaction with chemotherapeutic agents such as the taxanes. [18][19][20] The bi-sh-STMN1 incorporates two stem-loop structures in an expression construct promoting both cleavagedependent and cleavage-independent RNA-induced silencing complex (RISC) assemblies thereby generating RISC-associated mature effector small RNAs with multiple independent gene silencing activities. On the basis of the observation that miRNAs are associated with both non-nucleolytic (Ago1, 3,4) and nucleolytic Ago2-containing RISC and siRNAs with the nucleolytic Ago2, the novel bifunctional strategy specifically promotes the loading of miRNA-like effector molecules onto the cleavage-independent RISC as well as the accumulation of siRNA effector molecules by the cleavagedependent (Ago2 containing) RISC.…”
Section: Introductionmentioning
confidence: 99%
“…The contention was further supported by the demonstration that stathmin knockdown increased the sensitivity of glioma cells in vitro and in vivo [11]. Whether a single modification at the most sensitive lysine or modification at multiple lysine residues in the proteins is required to confer chemosensitivity of 1p −/+ gliomas remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously conducted proteomic profiling on two types of malignant glioma cell lines, one with normal chromosome 1p (1p +/+ ) and resistant to nitrosourea chemotherapy and the other missing a region of chromosome 1p (1p +\− ) and sensitive to nitrosourea chemotherapy. We showed that stathmin was significantly down-regulated in the 1p +\− cells [11]. Since stathmin gene is localized at chromosome 1p36.11, we suspected that a decrease in stathmin protein might account for sensitivity of 1p +/− gliomas to chemotherapy with nitrosourea derivatives such as CCNU (lomustine, 1-(2-chloroethyl)-3-cyclohexyl-1-nitroso-urea) or BCNU (1,3-bis (2-chloroethyl)-1-nitrosourea).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Further, overexpression of SIRT2 resulted in perturbation of microtubule network and reduced colony formation suggesting SIRT2 may act as tumor suppressor in glioma. Ngo et al, used a 2D-DIGE based proteomic approach to identify differences in protein expression between two glioma cells which differ in their chromosome 1p status (Ngo et al, 2007). The rational for this study is that 1p+/-anaplastic oligodendroglioma patients respond better to chemotherapeutic agents like procarbazine, 1-(2-chloroethyl)-3-cyclohexyl-l-nitrosourea, and vincristine.…”
Section: Glioma Tumor Tissue and Cell Line Based Studiesmentioning
confidence: 99%